Examining individual and school characteristics associated with child obesity using a multilevel growth model. (March 2015) - Miyazaki, Yasuo; Stack, Maria
Abstract: The childhood obesity epidemic continues to be a serious concern in the U.S., disproportionately affecting low socioeconomic and minority groups. Because many interventions are based in schools, both individual and school factors contributing to obesity were examined in this study. Employing data from the Early Childhood Longitudinal Study, Kindergarten Class of 1998–1999 (ECLS-K), a three level hierarchical linear model was used to estimate children's body mass index (BMI) growth trajectories within their school contexts. Results indicated an inverse relationship between BMI and socioeconomic status (SES), except for black males. Additionally, results showed that low school SES and rural locality of the school were school-level risk factors of obesity. Lastly, a major portion of the between-schools variance was explained by aggregated student characteristics, indicating that students were more likely to attend schools with peers of similar BMI who had similar SES and race/ethnicity, supporting a school-level compositional effect associated with obesity. Highlights: Identified a school compositional effect associated with child obesity. Identified low school SES and rural locality of schools as risk factors for obesity. Found that black males had an inverse relationship between SES and BMI before fifth grade.